Amniotic epithelial cells damage by oxidative stress in cases of diffuse chorioamniotic hemosiderosis. Issue 10 (5th August 2019) - Iizuka, Takashi; Ono, Masanori; Masumoto, Sakiko; Mitani, Yusuke; Yamazaki, Rena; Fujiwara, Hiroshi
Abstract: The amniotic membrane plays an important role in the physiological maintenance and protection of the embryo. Indeed, dysfunction of the amniotic membrane is thought to have an adverse effect on the continuation of pregnancy. In this report, we examined the pathological changes in the amniotic epithelium in three cases of diffuse chorioamniotic hemosiderosis (DCH) and investigated the cause of necrosis of the amniotic epithelial cells and its relationship with oligohydramnios. Diffuse chorioamniotic hemosiderosis was confirmed in all three cases. More extensive amniotic epithelial necrosis led to more severe hemosiderosis. Immunostaining for 8‐hydroxy‐2′‐deoxyguanosine, a marker of oxidative stress, was positive in the amniotic epithelial cells. We speculate that oxidative DNA damage of the amniotic epithelium occurs by decomposition products of blood cells in cases accompanying subchorionic hematomas and pathological DCH. Furthermore, disorder of the amniotic epithelium may disrupt the balance of the amniotic fluid volume and cause oligohydramnios.